Counter piracy programming and potential barriers to reintegrating Somali pirates: an African restorative justice critique - Gilmer, Brittany V. (International journal of law, crime and justice, 2019)
Since 2009, more than 300 Somali pirates have been prosecuted and imprisoned in East Africa using the United Nations Office on Drugs and Crime "regional model for prosecuting pirates". The vast majority of these piracy prisoners have been repatriated to Somalia and are slated to complete their sentences and return home within the next five years. However, members of Somalia's coastal communities continue to express anger and resentment towards former pirates—raising questions about the feasibility of reintegration. Drawing from African Criminology literature, this paper seeks to unpack how previous counter piracy programming helped foster an anti-piracy environment that also may have inadvertently created barriers to the eventual reintegration of former pirates. In doing so, we locate points of intervention and theorize how themes from African restorative justice can help decolonize counter piracy programming and inform a more Somali-driven approach to achieving justice for victims of piracy.